DINAMIKA PROSES KEBIJAKAN ANGGARAN PERUSAHAAN DAERAH AIR MINUM TIRTA SIAK KOTA PEKANBARU (TAHUN 2008-2012) - Armanda Sativa Graha; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aimed to describe the actors involved in the process of budget policy PDAM Tirta Siak in improving the performance of the company responsible for providing clean drinking water for the citizens of the city of Pekanbaru . Phenomenon that will be seen is the process of budget policy in 2008-2012. The usefulness of this study are as material information regarding the use of budgetary funds provided to PDAM Tirta Siak or other funds that go to the PDAM Tirta Siak , as well as the elements are concerned that use and know about the utilization of these funds so that customers and the general public know about the existence of and utilization of these funds .The method used in this study is qualitative methods of data that can not be expressed in terms of numbers but in the form of an explanation that describes the shape of the state , a process , a particular event . Data collection techniques using interview techniques , documentation and observation .To implement the required policies based on the concept Ndraha best choice within the limits of the competence of the relevant actors and institutions and formally binding . From the research it can be concluded that the budget policy in the years 2008-2012 PDAM Tirta Siak still not optimal due to the lack of cooperation between the Government and the company and other parties related to the PDAM Tirta Siak .Keywords : policies, performance, budget, government, society.